PENGARUH KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMK KANSAI PEKANBARU - Andoko Ageng Setyawan; Dumora Simbolon (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
ABSTRACTThe aim of this research is to know influence of emotional intelligence toward student’s mathematic score in SMK Kansai Pekanbaru. The Population of this research is all students who number 191 students in SMK Kansai Pekanbaru at the academic years 2016/2017. The instrument used in the research is emotional intelligence questionaire. The data were descriptive and quantitative analyzed using linear and regression test. The result of this research showed that were influenced emotional intelligence toward student’s mathematic score. The linearity score is 0.042 which lower than significant score is 0.05. It has linear connection between emotional intelligence and mathematic score. And the regression score is 0.044 which lower than significant score is 0.05 until there were influenced emotional intelligence toward student’s mathematic score. The Determination coefficient score   is 0.021, the mean of that emotional intelligence factor influenced toward student’s mathematic score until 2.1%, and more of that influenced by other factors. The result of regression analize got constant score is 53.77 and regression coefficient for emotional intelligence variable is 0.25. Therefore, the simple regression equation is Y = 53,77 + 0,25X. Keywords: Emotional Intelligence, Mathematic Score